Social Norm Incentives for Network Coding in Manets - Chuchu Wu; Gerla, Mario; van der Schaar, Mihaela (IEEE/ACM transactions on networking, 2017)
The performance of mobile ad hoc network transmissions subject to disruption, loss, interference, and jamming can be significantly improved with the use of network coding (NC). However, NC requires extra work for forwarders, including additional bandwidth consumption due to transmitting overheads for redundant NC packets and additional processing due to generating the NC packets. Selfish forwarders may prefer to simply forward packets without coding them to avoid such overhead. This is especially true when network coding must be protected from pollution attacks, which involves additional, often processor intensive, pollution detection procedures. To drive selfish nodes to cooperate and encode the packets, this paper introduces social norm-based incentives. The social norm consists of a social strategy and a reputation system with reward and punishment connected with node behavior. Packet coding and forwarding are modeled and formalized as a repeated NC forwarding game. The conditions for the sustainability (or compliance) of the social norm are identified, and a sustainable social norm that maximizes the social utility is designed via selecting the optimal design parameters, including the social strategy, reputation threshold, reputation update frequency, and the generation size of network coding. For this game, the impacts of packet loss rate and transmission patterns on performance are evaluated, and their impacts on the decision of selecting the optimal social norm are discussed. Finally, practical issues, including distributed reputation dissemination and the existence of altruistic and malicious users, are discussed.